An ill-appearing child with skin lesions and respiratory distress - Bernardo, Miguel; Igreja, Ana Isabel; Carvalho, Joana; Pereira, Helena (BIRTH AND GROWTH MEDICAL JOURNAL, 2023)
Primary infection with varicella-zoster virus (VZV) commonly occurs during childhood, generally with benign clinical course. The authors describe the case of a non-immunized eight-year-old girl with primary varicella infection complicated by a rare pulmonary finding: necrotizing pneumonia. Patient management and the spectrum of pulmonary complications in this setting are discussed.